Cost effective solution for energy efficiency in urban water supplies: Developing countries - Rudra Narsimha Rao, G. (Research India Publications, 2014)
In several developing countries, the share of urban water utilities' electrical energy consumption is over 5 of national electricity production. Energy cost is usually between 40 to 60 of the total operating cost of an urban water supply system. In urban water supply systems 90 of this electrical energy is consumed by pumps. The issues pertaining to developing countries are different than developed countries in this particular area. A huge sum of town council budget amount goes for paying electrical utility bills. The cost savings in water supply can lead to effective quality services (such as education, health, water and sanitation) to the local communities. One of the essential elements for optimizing energy cost of urban utilities is data monitoring and analysis. In the paper, case studies are presented to show-case importance of data analysis. Understanding of present tariffs and operational improvements itself results into a significant cost savings. A small improvement in pumping efficiency would yield significant reduction in energy consumption, which would in turn lead to reduction of carbon emissions to the atmosphere. Several energy efficiency studies show that there is a significant scope for energy costing savings in urban water pumping operations. However, a key barrier for carrying out energy efficiency improvement programme is the lack of knowledge and skill sets among the operational staff. To assist the water utility staff a web based interactive tool has been developed for identification of energy cost saving opportunities. The tool will contain the elements such as selection of appropriate measures, implementation and day-to-day management, and a monitoring system for the water works. The implications due to the use of such an online tool and its benefits are deliberated in the paper. Â© Research India Publications.